IMPLEMENTASI PEMBELAJARAN INKLUSI PADA SISWA DENGAN KESULITAN MEMBACA DI KELAS II SDN 30 PALEMBANG - Dilla, Ulfa; Murniviyanty, Liza; Puspita Sari Jaya, Melinda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the presence of students with special needs who experienced reading difficulties in inclusive classrooms at SD Negeri 30 Palembang. Reading difficulties may hinder students’ understanding of learning materials and learning processes, requiring appropriate instructional strategies and media. This study aimed to describe the implementation of inclusive learning for students with reading difficulties, particularly the strategies and media used by teachers. A descriptive qualitative method was employed involving the principal, Grade II A and II D teachers, and parents of students with special needs. Data were collected through observation, interviews, and documentation and analyzed using the Miles and Huberman model. The findings revealed that teachers applied gradual approaches, repetition methods, and behavioristic strategies through repeated reading exercises. The instructional media used included textbooks and alphabet posters. Teachers also provided assistance, motivation, and adjustments to assignments and assessments according to students’ abilities. The implementation of inclusive learning has been carried out effectively in supporting the development of students’ reading skills.